The Relationship Between Family-Centered Stimulation And Cognitive Development Of Children Age 5-6 Years In Akad Village - Susi lawati; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
The number of early childhood children in Kampung Akad, Pesisir Selatan Regency who experience delays in cognitive development is the background of this research. The cause of the slow cognitive development of children is thought to be due to the lack of stimulation provided by the family. This study aims to see an overview of stimulation in the family, a description of children's cognitive development, and the relationship between stimulation in the family and the cognitive development of children aged 5-6 years.his type of research is quantitative with a correlational approach. The population in this study were mothers who had children aged 5-6 years, while for the sampling using simple random sampling. Data collection techniques using a questionnaire, while for data analysis using the percentage formula and Spearmen Rho. The results showed that a) stimulation in the family was still low; b) children's cognitive development is still very low; and c) there is a significant relationship between stimulation in the family and the cognitive development of children aged 5-6 years.Keywords: Stimulation, cognitive development, family